RESPON KESUKAAN PANELIS TERHADAP COOKIES DENGAN SUBSITUSI TEPUNG BIJI ALPUKAT (Persea americana mill) dan PENAMBAHAN BUBUK KAYU MANIS (Cinnamomun burmanni) - Hasbiyah, Hasbiyah; Wulandari, Anita; Susanti P, Tiurma Wiliana; Rosida, Dwi Agustiyah (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Avocado seeds have not been optimally utilized, despite containing a significant amount of starch, approximately 80.1%. This makes avocado seeds a potential alternative starch source ready to be processed into various products, such as cookies. However, the limitation of avocado seed flour lies in its slightly musty aroma, necessitating the addition of flavor enhancers like cinnamon. This study aimed to determine the panelists' preference for cookies with wheat flour substituted by avocado seed flour (ASF) and the addition of cinnamon powder (CP) as a product diversification effort. The formulation of wheat flour substitution with ASF and the addition of CP, comprising F0 (no substitution and addition), F1 (15% ASF substitution + 2% CP), F2 (20% ASF substitution + 3% CP), and F3 (25% ASF substitution + 4% CP). Cookies were evaluated by 30 panelists based on color, aroma, taste and texture using an organoleptic test five-point Likert scale (strongly like, like, somewhat like, dislike, strongly dislike). Results indicated that for the color parameter, F1 (56.7%) was the most preferred treatment by most panelists. For aroma, taste, and texture parameters, treatment F2 was the most preferred by the majority of panelists, with 46.7% liking the aroma, 50% liking the taste, and 63.3% liking the texture.